UNIVERSITY RANKING: SOCIOLOGICAL SUPPORT - Ivan E. Zadorozhnyuk; Sergey V. Kireev (Высшее образование в России)
The article addresses a question of sociological provision of university ranking problems and procedures. The data of university rankings of 2015-2017 is provided, the sociological interpretation of their dynamic is given and the conditions of the Russian universities assessment are discussed. The authors characterize the provision of the accelerated promotion in rankings of National Research Nuclear University "MEPhI", the university that has the leading position in the Russian ranking systems and now is raising its position in the international ranking systems. The authors give recommendations for more sociologically consistent provision of ranking criteria, discuss the prospect of creation and status securing of the Russian university ranking system.